Distribution of Mangroves in Kedah, Malaysia: A Remote Sensing and Ground-Truth Based Assessment - Kamil, E.A. (IOP Publishing Ltd, 2020)
Mangroves are acknowledged for its ability in attenuating waves. The 2004 tsunami evidenced that mangroves shielded area encountered minimal damages compared to the unprotected coastlines. However, the status of mangroves nowadays is declining at an alarming rate due to natural disaster threats and anthropogenic factors. This study hereby aims to assess the distribution and species of mangroves in Kedah. Landsat-8 OLI images were utilized for mangroves distribution and species mapping by using GIS software. A number of 43 points were surveyed during ground-truthing in order to verify the mapping produced. The maps revealed that mangroves are abundantly grow in estuaries of Merbok-Kuala Kedah, and Langkawi. Five species from two families of mangroves were found which are including Rhizophora Apiculata, Avicennia Marina, Rhizophora Mucronata, Avicennia Officianalis, and Avicennia Alba, in order of dominance. Current mangroves coverage should be conserved and protected from any threats and human activities since a loss of approximately 2308 hectares of mangroves were observed compared to the status in 2012. Â© Published under licence by IOP Publishing Ltd.